Efficacy of Intra-Articular Ketorolac and Bupivacaine on Postoperative Pain Relief after Arthroscopic Anterior Cruciate Ligament Reconstruction: A Randomized Double-Blind Study - Sathonphanit, Supahsak; Thani, Sakda; Thanomsingh, Pachin (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: The purpose of our study was to determine whether there is any additional benefit to adding ketorolac, a non-steroidal anti-inflammatory drug (NSAID), to bupivacaine compared to bupivacaine alone in patients undergoing anterior cruciate ligament reconstruction (ACLR) surgery. Methods: Fifty-two American Society of Anesthesiology I-II patients undergoing arthroscopic ACLR under spinal anesthesia were randomly assigned to one of two groups: group A (10 mL of bupivacaine 0.25% with ketorolac 60 mg) and group B (10 mL of bupivacaine 0.25%). At the end of the procedure, 10 mL of each drug was administered intra-articularly. The dose of intravenously administered analgesic medication (morphine) was calculated based on the patient's body weight and visual analog scale (VAS) score. The postoperative time to rescue analgesia, 24-hour analgesic requirement, VAS score at time of rescue (T-rescue), and findings at rest and during movement were observed. Results: The VAS score at the time of rescue analgesic significantly lower in group A than in group B (33.85 ±19.61 ; 56.15±21.92) (p < 0.001). Group A had significantly lower 24-hour analgesic consumption than group B (0.28±0.07 ; 0.39±0.09) (p < 0.001).the mean duration of analgesia was longer in group A than in group B (320 minutes ; 235 minutes )(p = 0.194) however, this difference was not statistically significant. Conclusions: Intra-articular administration of a combination of ketorolac and bupivacaine resulted in a significantly longer duration of analgesia and reduced morphine use in the 24-hour postoperative period and is an effective option for reducing postoperative pain.